2014
DOI: 10.3109/00016489.2014.905702
|View full text |Cite
|
Sign up to set email alerts
|

Variations in treatment of peritonsillar abscess in four Nordic countries

Abstract: A total of 73 physicians (90%) replied. The largest differences arose in treating patients with intravenous versus per oral antibiotics, and treating as inpatients versus outpatients. In Finland, 50% of PTA patients aged >16 years were treated as inpatients and 50% as outpatients, whereas the respective quotas in Sweden were 9 and 91%, Norway 19 and 81%, and Denmark 33 and 67%. Of Finnish physicians, 30% treated their patients primarily with oral antibiotics, 70% with intravenous antibiotics; in Sweden 91 vs 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
4
19
0
1
Order By: Relevance
“…On the other hand, some authors have recommended needle aspiration rather than abscess incision and drainage, as sufficient and cost-effective treatment measures, while others observed that incision and drainage may overcome pain faster than aspiration [10,12,27,28]. Therefore, conclusions are still controversial.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, some authors have recommended needle aspiration rather than abscess incision and drainage, as sufficient and cost-effective treatment measures, while others observed that incision and drainage may overcome pain faster than aspiration [10,12,27,28]. Therefore, conclusions are still controversial.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, there are several host factor that may promote PTA, such as periodontal disease, smoking, compromised immunity and previous antibiotic use [8,9]. Treatment typically consists of antibiotics, with needle aspiration or drainage of the abscess, steroids, analgesia and fluid resuscitation [10]. Adequate, prompt treatment is mandatory because PTA can give rise, albeit rarely, to lifethreatening complications due to the infection spreading along the deep fascial planes of the neck and chest [11].…”
Section: Introductionmentioning
confidence: 98%
“…It is therefore remarkable that despite a lack of evidence abscesstonsillectomy prevails at least in some countries [10,12]. Unfortunately, NA is not documented Return-to-theatre 0 (0 %)…”
Section: Discussionmentioning
confidence: 96%
“…To date, no commonly accepted guidelines for the treatment of PTA exist and management protocols vary considerably among countries [10], even inside one country in different hospitals [13]. The lack of a gold standard for therapy indicates that there is no ''right'' or ''wrong''.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation